Prevalencia de Helmintos Enteroparasitos Zoonoticos y Factores asociados en Caninos Domésticos (canis familiaris) en el Barrio el progreso de la Parroquia San Juan de Pastocalle. - Unapucha Tenorio, Gissela Paola (2018)
This research project is based on the recording of data on the prevalence of enteroparasites in domestic canines (canis familiaris) and the factors associated with the age, sanitary and nutritional conditions of dogs to show that the percentage of parasitosis it is located in the Progreso district of Pastocalle del Cantón Latacunga, which was carried out by a population test and laboratory tests to determine the incidence of the same in the livestock area. Fecal sampling was performed on 75 dogs. The diagnosis was made using the coproparasitological method (33% zinc sulphate). Which was placed in the samples in the mixed containers and strained, allowing them to settle for later observation under a microscope? Of the 75 samples analyzed in the laboratory, 68 cases were positive for parasitosis, which represented 90.67% and 7 negative cases that represented 9, 33% of the positive cases, son for anointing 29.33%, ascaris 5.33 %, toxocara 6.67% and ancylostoma 49.33%. The positive cases found in canines from 0-12 months are 16 patients representing 21.33%, in positive cases in canines from 1-5 years, 48 cases are represented, representing 64.00% and in dogs older than 5 years, were 5% of those who represented 100%, the percentage of 97.01% and 2.94% with a moderate parasitic load were finally from the Barrio del Progreso de San Juan. Pastocalle there is a prevalence mainly of Ancylostoma in the age comprised from 1 to 5 years with a moderate prevalence respectively